A Novel Dnmt3a1 Transcript Inhibits Adipogenesis - Abdalla, Bahareldin A.; Li, Zhenhui; Ouyang, Hongjia; Jebessa, Endashaw; Sun, Tianhao; Yu, Jia-ao; Cai, Bolin; Chen, Biao; Nie, Qinghua; Zhang, Xiquan (Frontiers in Physiology, 2018)
DNA (cytosine-5)-methyltransferase 3a (Dnmt3a) is an enzyme that catalyzes the transfer of methyl groups to specific CpG forms in DNA. In mammals, two variant transcripts of Dnmt3a have been successfully identified. To the best of our knowledge, no Dnmt3a transcripts in an avian have been successfully identified. This study was performed to detect different transcripts of Dnmt3a in chickens and to examine whether a novel Dnmt3a transcript named Dnmt3a1 may regulate adipogenesis. In addition to cloning, sequencing, transcript detection, and expression studies, a novel Dnmt3a1 transcript overexpression and knockdown were conducted to explore the potential role of Dnmt3a1 in preadipocyte proliferation and early stage of adipocyte differentiation. Here, we detected a novel Dnmt3a1 transcript in chicken abdominal fat tissue which differs from Dnmt3a by lacking 23 amino acids at the exon-1/exon-2 border. Dnmt3a1 mRNA was ubiquitously expressed in a variety of tissues or cells and highly expressed in chicken adipose tissue/cells. Expression of Dnmt3a1 was regulated under different physiological conditions including aging, fasting and high-fat diet. In addition, overexpression of Dnmt3a1 significantly decreased preadipocyte proliferation and induced cell cycle arrest while its inhibition increased cell-proliferation and S-phase cells. Furthermore, overexpression of Dnmt3a1 significantly up-regulated the mRNA level of cell cycle-related genes, such as CDKN1A, CDKN1B, CCNB3, CCND2, CCNG2, CDKN2B, and CDK9, or the protein level of CDKN1A, CDKN1B, and CCNG2. Conversely, knockdown of Dnmt3a1 by siRNA had the opposite effects. Moreover, during early adipocyte differentiation, overexpression of Dnmt3a1 significantly decreased the mRNA and protein level of PPAR-γ, C/EBP-α, ADIPOR1and STAT3, and mRNA levels of FAS, LEPR, LPL, PRKAB2, and ATGL. In contrast, their expression was significantly increased after knockdown of Dnmt3a1. Taken together, we identified a novel transcript of Dnmt3a, and it played a potential role in adipogenesis.